2015
DOI: 10.1111/acem.12706
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Performance of the Richmond Agitation Sedation Scale for Detecting Delirium in Older Emergency Department Patients

Abstract: Objectives Delirium is frequently missed in older emergency department (ED) patients. Brief (<2 minutes) delirium assessments have been validated for the ED, but some ED health care providers may consider them to be cumbersome. The Richmond Agitation Sedation Scale (RASS) is an observational scale that quantifies level of consciousness and takes less than 10 seconds to perform. The authors sought to explore the diagnostic accuracy of the RASS for delirium in older ED patients. Methods This was a preplanned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 16 publications
(26 reference statements)
2
67
1
4
Order By: Relevance
“…Inouye has shown that the presence of sensory impairment, dementia, older age and the hypokinetic variant of delirium increase the odds of delirium to be undetected by nurses. 17 In this study, the simple clinical observation, without using standardized diagnostic tools led to a rate of underecognition which was around 70%, significantly lower if compared to the rate of delirium detected by a team of researchers trained in the use of diagnostic tools. 17 However, also untrained physicians tend to frequently overlook delirium.…”
Section: Reviewmentioning
confidence: 66%
See 2 more Smart Citations
“…Inouye has shown that the presence of sensory impairment, dementia, older age and the hypokinetic variant of delirium increase the odds of delirium to be undetected by nurses. 17 In this study, the simple clinical observation, without using standardized diagnostic tools led to a rate of underecognition which was around 70%, significantly lower if compared to the rate of delirium detected by a team of researchers trained in the use of diagnostic tools. 17 However, also untrained physicians tend to frequently overlook delirium.…”
Section: Reviewmentioning
confidence: 66%
“…17 In this study, the simple clinical observation, without using standardized diagnostic tools led to a rate of underecognition which was around 70%, significantly lower if compared to the rate of delirium detected by a team of researchers trained in the use of diagnostic tools. 17 However, also untrained physicians tend to frequently overlook delirium. 51 There are more than twenty-four diagnostic tools for delirium, the most commonly used is the confusion assessment method (CAM).…”
Section: Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…1113 However, none of the previous studies has focused specifically on patients with delirium and dementia. Han and colleagues 12 found a RASS score other than 0 to have a very good sensitivity (84%, 95% CI: 73.8% to 94.2%) and specificity (87.6%, 95 % CI: 84.2% to 91.1%) for the detection of delirium in 406 older patients admitted to an emergency department (ED). Interestingly, a RASS score > +1 or < –1 was nearly diagnostic for delirium in this population, 12 providing the busy ED setting with a fast and valuable tool for the screening-diagnosis of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…12 In this group were included older patients admitted to an academic, tertiary care emergency department July 2009 to February 2012. Delirium was diagnosed using a comprehensive consultation-liaison psychiatrist assessment with the DSM-IV-TR criteria, while dementia was ascertained using the clinical records and IQCODE.…”
Section: Methodsmentioning
confidence: 99%